Pengaruh Media Promosi terhadap Minat Belanja Khalayak di Giant Extra Plaza Yogya (Survei Masyarakat RW 11 Kelurahan Curug, Bogor) - Intan Tri Kusumaningtias; Prasetyo Adi Nugroho (Media Bahasa, Sastra, dan Budaya Wahana, 2019)
AbstractIn a visual design marketing communication is the one thing that is interesting to learn and discover. The development in this area has a tight bond with the increase of the realization that could be the benefit of the straight-forward information to the society.In creating a visual design that would be published to the Giant Express or Giant Extra customers, they would want to give the same visual to the customers with what are the product they promote through visual design. Once the customers have the same point of view, the company could build a positive bond with customers.This research was conducted to see the impact of media promotion on the regular customers at Giant Extra Plaza Yoga. A quantitative research is used. According to Hasan (2002:21) “research method a way to connects with ongoing research, with systematic step”. He used the systematic method, meanwhile quantitative method according to Kriyantono (2007:55)“research with quantitative can be found in numbers, numbers or frequency can be defined to pictured different kind of definitions. Methodology has a objective principle, because the result depending on the research from the customers. Hence, research quantitative method is a research that gone through and explained a problem in a systematic step. Ergo, the writer chooses quantitative method because it has structure and finding the right way in analysing data.Researcher using descriptive correlation Hasan (2002: 22-23) explained correlation descriptive is the type of description that shown variable after variable. This method aims to gather actual information’s in detail that explained it has happened. However, correlation is used to find the connection between variables in details. This type of correlation aimed for detailed searched on how far one variable to the other in one factor regarding the variation of another.According to the processing and result, we could conclude the coefficient value correlation (r) the value is 0,258 acting positives. Hence, could be interpret that the media promotion has low connection to the customers in RW II Kelurahan Curug, Bogor. So the result os not attracted by the customers.From the result regression analysis t equals to 2.285 and t table equals to 1.992. So if you count t table (2,2851992) with significant level 0,0000,05. Ho rejected and Ha accepted it means that the impact of significant between media and promotion of customers in RW II Kelurahan Curug, Bogor.Result analysis regression is the value R square  0.258 it means 74,2% willing to shop by the influence of the writer, for example the appearance of the supermarket and the type of the products presented by the media promotion. Keywords: Media Promotion, Regular Customers